Muzyczno-synestezyjna przestrzeń Mariny Cwietajewej w eseju autobiograficznym „Matka i muzyka” - Ojcewicz, Grzegorz (Acta Neophilologica, 2020)
The author presents Marina Tsvetaeva’s musical and synaesthetic space on the basis of My Mother and Music, her autobiographical essay. Synaesthesia, although present in the life of Tsvetaeva as a young child and adult poet, is not especially depict-ed in this particular piece of work. The writer chose her memories which encompass a significant period of time from her birth to her 42nd birthday as her main narrative focus. The musical sphere of the young child was presented through the piano and its attributes (the keyboard, pedals, music stand, metronome, notes, piano stool), which were a source of various – both positive and negative – experiences for this sensitive girl. Marina Tsvetaeva’s mother, unfulfilled as a pianist, undoubtedly played a toxic role in her musical education. Maria Tsvetaeva “drowned and killed her daughters with music”, making them feel an organic resistance towards required physical and mental efforts far too great for their age. The situation changed after her mother’s death when Marina could pour all her love for music into incredibly original lyric poetry, becoming one of the greatest writers of the 20th century.